Stigmatizing Attitudes Toward Depression Among Male and Female, Medical and Non-medical Major College Students - He, Haoyu; Wu, Qiuxia; Hao, Yuzhu; Chen, Shubao; Liu, Tieqiao; Liao, Yanhui (Frontiers in Psychology, 2021)
Background: Stigma is often reported to be a barrier to the treatment and rehabilitation of depression. However, little is known about stigma toward people with depression among college students in China. Methods: Using a questionnaire with a case vignette describing depression, a total of 1,056 students from nine colleges/universities in Hunan Province of China were included in this study. The questionnaire addressed the attitudes toward depression and the desire for keeping a distance from depressed individuals. The current study explored the stigma attitudes of college students toward people with depression and the desire for social distancing, as well as the gender (male and female) and major (medical and non-medical) differences. Results: Over half of the respondents agreed that people described in the vignette were “dangerous” (60.7%) and “could snap out of the problem” (58.7%). Compared with female students, males were more likely to agree that “If I had this problem, I would not tell anyone” (7.0 vs. 13.2%, p = 0.001); compared with non-medical students, medical students were more likely to agree that “The problem is a sign of personal weakness” (38.0 vs. 50.0%, p < 0.001). A lot of respondents would be unwilling to “marry into the family of people with depression” (71.1%) or “work closely with them” (45.1%). Compared with male students, females were more unwilling to “work closely with them” (40.3 vs. 47.5%, p = 0.026). Conclusion: This study found that a high proportion of Chinese college students showed stigma toward and desire for social distancing from people with depression, male students and medical major students showed higher stigma in some subscale items toward people with depression. The present results suggest that more anti-stigma interventions should be applied for Chinese college students to help prevent or reduce stigma attitudes toward people with depression.